Uptake of actinides by calcium silicate hydrate (C-S-H) phases. (November 2018) - Häußler, Verena; Amayri, Samer; Beck, Aaron; Platte, Tim; Stern, Tobias A.; Vitova, Tonya; Reich, Tobias
Abstract: The sorption of actinides (Th, U – Am) was studied in dependence of the solid-to-liquid ( S/L ) ratio (0.5–20.0 g/L) and the calcium-to-silicon (C:S) ratio. The C:S ratio was varied between 1.80 and 0.70 to simulate the changing composition of the C-S-H phases during cement degradation from high to low C:S ratios. The decrease of the calcium content in the C-S-H phases by time is accompanied by a decrease in pH in the corresponding suspensions from 12.6 to 10.2. X-ray photoelectron spectroscopy (XPS) of the C-S-H phases showed an increasing depletion of Ca on the surface with increasing C:S ratio in comparison to the composition of the solid phase as a whole. The sorption experiments were performed with the redox stable species Am(III), Th(IV) and U(VI), as well as the redox sensitive Np(V) and Pu(III). The average distribution coefficients R d for all investigated actinides are around 10 5  L/kg. The oxidation state of Pu retained by the C-S-H phases was investigated with high-energy resolution X-ray absorption near-edge structure (HR-XANES) spectroscopy. Samples with C:S ratios of 0.75 and 1.65 showed that the initially added Pu(III) was oxidized to Pu(IV) in the course of the experiment. Graphical abstract: Highlights: First investigation of Pu uptake by C-S-H phases combining batch experiments with Pu M5 -edge HR-XANES spectroscopy. Similar Rd values determined for Am(III), Pu(III), Th(IV), Np(V) and U(VI), independent of the C:S and S/L ratios. XPS measurements indicate a depletion of Ca at the surface of the C-S-H phases.